2013 Humaine Association Conference on Affective Computing and Intelligent Interaction 2013
DOI: 10.1109/acii.2013.85
|View full text |Cite
|
Sign up to set email alerts
|

Reading Personality: Avatar vs. Human Faces

Abstract: Studies have suggested that facial appearance leads to judgment of a person's character, e.g. wide-faced males are considered aggressive and untrustworthy, large eyes make a person appear honest and non-dominant, and short ears and nose give impressions of warmth and honesty. In this study we investigate whether we make similar judgment with an avatar's face. Using SecondLife avatars as stimuli, we employ PairedComparison Tests to determine the implications of certain facial features. Our results suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Appearance has been observed to be utilized in making interpersonal judgments (Naumann et al, 2009), and this can extend to virtual avatars (Wang et al, 2013;Fong and Mar, 2015). It was observed that judges made relatively consistent inferences based on avatar appearance alone (Wang et al, 2013;Fong and Mar, 2015), and more attractive avatars were rated more highly in an interview scenario (Behrend et al, 2012). How this might manifest with robot avatars, in particular in the interaction between a robot appearance and human voice communication, remains unclear and is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Appearance has been observed to be utilized in making interpersonal judgments (Naumann et al, 2009), and this can extend to virtual avatars (Wang et al, 2013;Fong and Mar, 2015). It was observed that judges made relatively consistent inferences based on avatar appearance alone (Wang et al, 2013;Fong and Mar, 2015), and more attractive avatars were rated more highly in an interview scenario (Behrend et al, 2012). How this might manifest with robot avatars, in particular in the interaction between a robot appearance and human voice communication, remains unclear and is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Since ECAs can mimic naturalistic human communication, there are studies comparing human-human interaction with human-ECA interaction. According to Wang, Joel, et al [38], people tended to treat VAs similarly to real human beings. McRorie et al [29] implemented four stereotypical personalities in the virtual agents.…”
Section: Human-eca Impression Formationmentioning
confidence: 99%
“…It was observed that judges made relatively consistent inferences based on appearance alone [8], [9], and more attractive avatars were rated more highly in an interview scenario [22]. However, how these inferences interact with communicative behaviours of operators has yet to be examined.…”
Section: B Tele-operationmentioning
confidence: 99%
“…This is in light of previous work on personality judgements of virtual avatars based on their appearance [8], [9].…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation